Varietal release guide: Policies and procedures in Colombia - Rivas, Lorenzo; Ocampo, John; Rodriguez Machado, David; Andrade, Robert (2024)
Colombian seed laws and policies have undergone significant evolution to regulate and facilitate the innovation process. Beginning with the establishment of the Ministry of Agriculture, the founding of ICA, and culminating in the present regulations, the contemporary landscape demonstrate a clear regulatory structure for the innovation of seed genetic material. This regulatory framework consistently seeks innovation and improvements to align with the nutritional needs of not just the Colombian population but also on a global scale.